Cross-Linguistic Representation of National Identity through Proverbs (Insights from Abdulla Qahhor and O. Henry) - Qodirova, Ziyodaxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This study examines the cross-linguistic representation of national identity through proverbs in the literary works of Abdulla Qahhor and O. Henry. Both authors employ proverbs as a tool to communicate moral and cultural codes inherent to their societies. The research investigates how linguistic structure and pragmatic function of proverbs embody national consciousness, emphasizing the reflection of Uzbek collectivism and American individualism. Through comparative textual analysis, the paper highlights the linguistic creativity and cultural symbolism of proverbs as vehicles of national identity in literature.